Side Effects of COVID-19 Vaccines Among Diabetic Subjects and Healthy Individuals - Khan, Fareena; Khan, Muhammad Taimur; Zaman, Sana; Mujtaba, Sadaf; Batool, Aeliya; Ghanghro, Zohra; Anwar, Adnan; Hashmi, Atif A (Curēus (Palo Alto, CA), 2023)
Objectives Vaccinations protect against disease through various ways, but the process of developing immunity might result in side effects. This study determined the immediate side effects of coronavirus disease 2019 (COVID-19) vaccination among patients with diabetes and non-diabetic participants. Methods This multi-center, cross-sectional study was conducted in multiple hospitals in Karachi, Pakistan. The duration of the study was six months, from March 1, 2022, to August 31, 2022. A total of 1150 participants who received one of the COVID-19 vaccines, for instance, Sinopharm, AstraZeneca, Sinovac, and Pfizer (double or booster doses) were included in the study and allocated into two groups: diabetics (n=540) and non-diabetics (n=610). The chi-square test was used to compare the frequency of side effects between diabetic and non-diabetic participants. The association between means of demographic variables such as age and weight was compared using an independent t-test. Results The study findings showed that the mean age of the group with diabetes was 46.73±14.98 years and that of the non-diabetic group was 44.01±14.80 years with a significant difference between them (p=0.002). The majority of participants, 187 (34.6%) patients with diabetes received Pfizer, while 234 (38.4%) non-diabetic participants received Sinovac. Following the first dose, side effects were higher in patients with diabetes. Burning at the injection site, fever, and pain were the most commonly reported side effects in patients with diabetes following the first dose. Additionally, following the second dose, burning at the injection site, muscular pain, fever, and pain were the most commonly observed side effects, with a significant association among diabetic and non-diabetic participants (p<0.001). Conclusion Diabetes is a prevalent comorbidity in individuals infected with COVID-19, and patients with diabetes report more side effects from immunization than non-diabetic participants. The most commonly reported side effects of the vaccine in diabetic participants were observed to be burning at the injection site, fever, muscle and joint pain, and swelling at the injection site. Additionally, participants with and without diabetes reported feeling satisfied with their vaccines.